Sintering study and constitutive modeling of 316L stainless steel microstructured parts fabricated by μPIM - Liu, Lin (2009)
Powder injection molding (PIM) of parts having structures in the sub-millimeter range, also known as micro powder injection molding (μPIM), is a technology of potential for mass production of these parts due to the unique combination of properties obtainable from PIM. μPIM comprises four processing steps: mixing, injection molding, debinding and sintering. Considering the dimensional regime of the microsize structures, control of sintering is important for microstructured parts in μPIM. Hence, the effects of size of microstructured parts on the grain growth and densification are studied is this research. In addition, a constitutive model is developed to depict the densification of microstructured parts. A circular disc of diameter 16 mm and 1.5 mm thick (sub-structure), with an array of 24x24 microsize structures with three different sizes, diameter 100 μm x height 200 μm, diameter 80 μm x height 196 μm or diameter 60 μm x height 191 μm, were molded using the in-house feedstock for the study. To investigate the effects of size of microstructured parts on the grain growth and densification, the debound microstructured parts were sintered at various time and temperatures after which the grain size and density of the sub-structure and three different microsize structures were characterized. It shows that the size reduction into micrometer regime increased densification. All the microsize structures were at the final sintering stage while the sub-structure was at the intermediate sintering stage within the temperatures studied. As compared to the microsize structures of diameter 100 μm and diameter 80 μm, the microsize structures of diameter 60 μm yielded the highest density within the temperatures studied. Analysis based on Brook, Coble and Herring’s models shows that the controlling mechanism for grain growth and densification varied for the sub-structure and various microsize structures, the result of which is useful for modeling sintering behavior of the microstructured parts. Since the grain number varies with sintering at the final sintering stage due to grain growth, a new sintering stress expression taking into account the variation in grain number was developed. A constitutive model was established to compute densification of the sub-structure and various microsize structures on the microstructured parts. In the model, Besson and Abouaf’s constitutive equation and Brook’s model for grain growth were used. The contribution of lattice diffusion, which was not included in Besson and Abouaf’s work, was considered here. The effects of pore location and boundary energy on the densification of the various microsize structures were discussed during modeling. The theoretical calculations using the model were compared with the experimental results of the sub-structure and various microsize structures. As the computed densities based on the simplified assumption that all the pores were located at four-grain junctions were similar to that computed where pores on two-grain interface and separated pores were included, the treatment of all pores located at four-grain junctions can be used in the model. Including the work done by grain boundary energy gave higher densities for all the microsize structures which were generally closer to the experimental results. The model approximately agreed with the experimental results.